ANALISIS RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013 - 2015) - Dewi Hastuti, 10.05.52.0201; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2017)
The purpose of this research is to know the influence of financial ratio to profit growth.The sample of this research are manufacturing companies listed on BEI from 2013-2015 were selected using purposive sampling method.The number of samples used counted 243 data from a population of 306 companies. The data used in this research is secondary data. The method of analysis used in this research is multiple linear regression analysis.The results show that Total Assets Turnover (TATO) and Inventory Turnover (ITO) has no effect on profit growth. Current Ratio (CR) and Debt to Equity Ratio (DER) has a negative effect on profit growth. Net Profit Margin (NPM) has a positive effect on profit growth.Keywords: Total Assets Turnover (TATO), Inventory Turnover (ITO), Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Profit Growth